Pendampingan Desain Iklan Media Sosial Untuk Meningkatkan Strategi Pemasaran Digital Dan Omzet Penjualan Produk Teaching Factory SMK Negeri 6 Yogyakarta - Wibawa, Eka Ary; Hakim, Arif Rahman; Ngadiyono, Ngadiyono; Farlianto, Farlianto; Makarim, Muhammad Harfiansyah (STMIK Royal, 2024)
Product marketing strategy in the digital business era need to utilize optimal use of social media platforms. According to the situational analysis, the target audience for community service was unable to create social media ads for teaching factory products. As a solution to this problem, the service team is committed to providing community service related to assisting in the design of teaching factory product social media advertisements for the target audience. There were 34 participants in this service activity consisting of students and accompanying teachers. The results of the service activities show that overall the activities ran successfully and smoothly. The evaluation results show that there has been an increase in the target audience's understanding of product design for social media advertising. Increased understanding can be seen from the ability to design product advertisements for social media posts by considering color composition, image quality, font size, typeface, and graphic design layout of social media advertisements. The success of implementing this service activity can also be reflected in the increase in sales turnover of teaching factory products.Keywords: advertising design; social media; sales turnover; products; teaching factory Strategi pemasaran produk pada era bisnis berbasis digital perlu memanfaatkan platform media sosial dengan optimal. Analisis situasi menunjukkan bahwa khalayak sasaran pengabdian kepada masyarakat belum mampu melakukan desain iklan produk teaching factory pada media sosial. Sebagai solusi atas permasalahan tersebut, tim pengabdi berkomitmen untuk melakukan pengabdian kepada masyarakat terkait pendampingan desain iklan media sosial produk teaching factory bagi khalayak sasaran. Peserta kegiatan pengabdian ini sebanyak 34 orang yang terdiri atas siswa dan guru pendamping. Hasil kegiatan pengabdian menunjukkan bahwa secara keseluruhan kegiatan berjalan sukses dan lancar. Hasil evaluasi menunjukkan bahwa terjadi peningkatan pemahaman khalayak sasaran tentang desain produk untuk iklan media sosial. Peningkatan pemahaman terlihat dari kemampuan mendesain iklan produk untuk postingan media sosial dengan mempertimbangkan komposisi warna, kualitas gambar, ukuran huruf, jenis huruf, dan tata letak desain grafis iklan media sosial. Keberhasilan pelaksanaan kegiatan pengabdian ini juga dapat tercermin dari adanya peningkatan omzet penjualan produk teaching factory. Kata kunci: desain iklan; media sosial; omzet penjualan; produk; teaching factory